Survival and performance of Sarsina violascens (Lepidoptera:Lymantriidae) larvae on Eucalyptus species and hybrids - Pereira, Jaqueline Magalhães; dos Santos, Tássia Tuane Moreira; Soliman, Everton Pires; Dias, Thaíse Karla Ribeiro; Baldin, Edson Luiz Lopes [UNESP]; Wilcken, Carlos Frederico [UNESP] (Springer Nature, 2022)
The defoliating caterpillar Sarsina violascens causes economic losses in Brazilian Eucalyptus crops. Information on the susceptibility of Eucalyptus species and hybrids to insect pests is scarce. As such, this study aimed to assess the development of S. violascens on Eucalyptus species and hybrids under laboratory conditions. Neonate caterpillars were reared on leaves of Eucalyptus grandis, E. urophylla, E. camaldulensis and E. globulus; and hybrids of E. urophylla x E.urophylla, E. urophylla × E. grandis, E. grandis × E. camaldulensis and E. urophylla × E. camaldulensis. Biological parameters such as instar and larval phase duration, pupal weight, adult longevity and fecundity, and eclosion rate were evaluated. Eucalyptus globulus is not an S. violascens host, leading to 100% larval mortality in the first instar. Eucalyptus grandis extended the larval phase of the insect and decreased larval survivorship and female pupal weight, resulting in high levels of deformity in adults and low egg eclosion, in addition to exhibiting significant antibiosis to S. violascens. Eucalyptus camaldulensis and VM-1 extended the larval period and reduced pupal weight. Eucalyptus urophylla was better suited to the development and reproduction of S. violascens than other Eucalyptus species and hybrids. E. grandis is a promising source of resistance to S. violascens. The use of resistant species and hybrids contributes to pest management, reducing the need for chemical control.
Keywords: Antibiosis; Defoliating caterpillars; Forest pest; Host-plant resistance; Purple moth